Peningkatan Kinerja Guru Dalam Pengembangan Evaluasi Hasil Belajar Melalui Supervisi Akademis Kepala MadrasahDi MTsN 7 Jombang Tahun Pelajaran 2019-2020 - Karim, H. (Balai Diklat Keagamaan Surabaya, 2020)
This study aims to determine the improvement in teacher performance in the development of evaluationof learning outcomes through the academic supervision of madrasa principals in MTsN 7 Jombang in 2019-2020 Academic Year. The action hypothesis in this study is as follows: Teacher performance indeveloping evaluation of learning outcomes can be improved through Academic Supervision in MTsN 7,Jombang, East Java, 2019-2020 Academic Year. The appl ication of academic supervision bymadrasah principals is effective in improving teacher performance in developing evaluation of learningoutcomes in MTsN 7 Jombang 2019-2020. This type of research is madrasah action research throughthe application of academic supervision Madrasah head with a descriptive qualitative approach. Thenumber of teachers who were the objects of this study were 14 teachers. Data obtained throughinterviews, observations, and tests. Technical analysis of data using quantitative and qualitativetechnical analysis and its implementation through 3 cycle. The results of the study include: improvingteacher performance through the academic supervision of madrasah principals very well. The results ofthe analysis showed that of the 14 teachers the average value reached; 59.64 % increased to 68.93 %and in cycle 3 increased to 76.43 %. The conclusion is the performance of teachers in developingevaluation of learning outcomes can be improved through Academic Supervision in MTsN 7 Jombang in2019-2020 Academic Year with a good predicate. The application of madrasah head academicsupervision is effective in improving teacher performance. Based on the results of the study above,improving teacher performance in the development of evaluations of learning outcomes throughthe academic supervision of the madrasah head toward the desired change reaching 85 % of his achievement, then the teacher’s performance is said to be effective. Thus the hypothesis proposed above can be accepted.